2018
DOI: 10.1080/15568318.2018.1431821
|View full text |Cite
|
Sign up to set email alerts
|

Verkehrsverbund: The evolution and spread of fully integrated regional public transport in Germany, Austria, and Switzerland

Abstract: Throughout the world, urban areas have been rapidly expanding, exacerbating the problem of many public transport (PT) operators providing service over different governmental jurisdictions. Over the past five decades, Germany, Austria, and Switzerland have successfully implemented regional PT associations (called Verkehrsverbund or VV), which integrate services, fares, and ticketing while coordinating public transport planning, marketing, and customer information throughout metropolitan areas, and in some cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 50 publications
0
28
0
4
Order By: Relevance
“…Within its city centre, Zurich's population density was 4,432 people per km² in 2015 and its suburban density was 651 people per km² in 2015. These figures are higher than several other large European cities such as Hamburg, Vienna, and Berlin (Buehler et al, 2019).…”
Section: City Profilementioning
confidence: 57%
“…Within its city centre, Zurich's population density was 4,432 people per km² in 2015 and its suburban density was 651 people per km² in 2015. These figures are higher than several other large European cities such as Hamburg, Vienna, and Berlin (Buehler et al, 2019).…”
Section: City Profilementioning
confidence: 57%
“…One review of the impacts of several fare integration schemes by Sharaby and Shiftan (2012) showed that in each case, ridership increased, as presented in Figure 27. A 2018 study by Buehler et al 132 examined how metropolitan regions in Germany, Austria, and Switzerland have successfully implemented regional public transport (PT) coordination through organizations called Verkehrsverbunde (VVB). The VVB typically include dozens of public and private transit entities but provide "one time-table, one fare, and one ticket."…”
Section: Smart Cards Do Not Necessarily Mean Fare Integrationmentioning
confidence: 99%
“…The coordination of public transport systems, not only through integrated fares but also through integrated ticketing and coordinated transport planning, marketing, and customer information, is a foundation for providing an attractive alternative to the car. Buehler, Pucher, & Dümmler [53] suggest that such coordination, in the form of so-called Verkehrsverbund, is a part of the explanation of why the modal share of private cars has fallen since 1990 in many German, Austrian, and Swiss metropolitan areas. In all six of their case studies, they argue that the integrated public transport associations have increased the quality and quantity of services, attracted more passengers, and reduced the proportion of costs covered by subsidies.…”
Section: Availability and Accessibility 431 Planning And Organisingmentioning
confidence: 99%